2019
DOI: 10.1021/jacs.9b09643
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene-Equipped Covalent Organic Framework: Light-Operated Reservoir

Abstract: Light-operated materials have gained significant attention for their potential technological importance. To achieve molecular motion within extended networks, stimuliresponsive units require free space. The majority of the so far reported 2D-extended organic networks with responsive moieties restrict their freedom of motion on account of their connectivity providing constrained free volume for efficient molecular motion. We report here a light-responsive azobenzene-functionalized covalent organic framework (TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 81 publications
3
97
0
2
Order By: Relevance
“…For example, Jiang et al reported an anthracene-based 2D COF, which can show structural transformations by alternating UV light irradiation and heating 38 . Trabolsi et al reported an azobenzene-equipped 2D COF that can be used as light-operated reservoir 41 . Unfortunately, although these systems have shown interesting stimuli-responsive properties, there still has some problems that need to be further improved, such as inefficient conversion.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jiang et al reported an anthracene-based 2D COF, which can show structural transformations by alternating UV light irradiation and heating 38 . Trabolsi et al reported an azobenzene-equipped 2D COF that can be used as light-operated reservoir 41 . Unfortunately, although these systems have shown interesting stimuli-responsive properties, there still has some problems that need to be further improved, such as inefficient conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized covalent organic framework could be effectively utilized for rhodamine B storage and on‐demand release ( Figure A). [ 205 ]…”
Section: Photoisomerization‐based Drug Releasementioning
confidence: 99%
“…Reproduced with permission. [ 205 ] Copyright 2019, American Chemical Society. B) Chemical structures of phototrexate in the trans and cis configurations.…”
Section: Photoisomerization‐based Drug Releasementioning
confidence: 99%
“…Also, they differ in their planarity with the trans form assuming a planar form with C 2h symmetry and the cis form assuming a nonplanar form with C 2 symmetry. 12 As such, the photoresponsive azobenzene has been used in incorporation with polymeric materials, 13,14 different nanostructured materials 15,16 and metal-organic frameworks [17][18][19] for energy storage applications.…”
Section: Introductionmentioning
confidence: 99%